2020
DOI: 10.1002/tht3.469
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy masking and the identity crowding debate

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…However, observers rarely depicted any of the letters of the target set or distorted versions of them when shown letter-like stimuli (4% of responses to the letter-like trials), and never any other letter (as shown by visual inspection). Interestingly, although most omission errors occurred for identical lines, we did not find any evidence for redundancy masking (Sayim & Taylor, 2019;Taylor & Sayim, 2020;Yildirim et al, 2020;Yildirim, Coates, & Sayim, 2021) for the letter-like E target (i.e., reporting two instead of three horizontal lines). Because participants were presented with on average nine letters before the letter-like E, and the letter or letter-like F preceded the letter-like E for seven out of ten participants, expectation of a letter and implicit or explicit comparisons with the relatively easy F-target could underlie the absence of redundancy masking (see also Yildirim et al, 2021).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, observers rarely depicted any of the letters of the target set or distorted versions of them when shown letter-like stimuli (4% of responses to the letter-like trials), and never any other letter (as shown by visual inspection). Interestingly, although most omission errors occurred for identical lines, we did not find any evidence for redundancy masking (Sayim & Taylor, 2019;Taylor & Sayim, 2020;Yildirim et al, 2020;Yildirim, Coates, & Sayim, 2021) for the letter-like E target (i.e., reporting two instead of three horizontal lines). Because participants were presented with on average nine letters before the letter-like E, and the letter or letter-like F preceded the letter-like E for seven out of ten participants, expectation of a letter and implicit or explicit comparisons with the relatively easy F-target could underlie the absence of redundancy masking (see also Yildirim et al, 2021).…”
Section: Discussioncontrasting
confidence: 74%
“…For example, in the letter-like A target, observers missed at least one of the two vertical lines in 80% of the trials (60% one line, 20% both lines). The strong dependence of errors on the target type and spatial relations between lines, as well as the near absence of errors for simple targets (e.g., targets consisting of only two lines) suggest that the observed errors were due to crowding between the target parts ("self-crowding"; Martelli, Majaj, & Pelli, 2005;Zhang, Zhang, Xue, Liu, & Yu, 2009), or redundancy masking, the reduction of the perceived number of repeated elements (Sayim & Taylor, 2019;Taylor & Sayim, 2020;Yildirim et al, 2020; see also Taylor & Sayim, 2018), when the target lines were highly similar.…”
Section: Discussionmentioning
confidence: 99%
“…In redundancy masking (RM), the perceived number of identical items is reduced ( Sayim & Taylor, 2019 ; Taylor & Sayim, 2018 ; Taylor & Sayim, 2020 ; Yildirim, Coates, & Sayim, 2020 ; Yildirim, Coates, & Sayim, 2021 ). For example, when presented with three identical, nearby letters in the visual periphery, observers frequently reported only two letters in a free naming and drawing task ( Sayim & Taylor, 2019 ) ( Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…Crowding mainly manifests itself in peripheral vision (for foveal crowding, see Coates, Levi, Touch, & Sabesan, 2018 ; Malania, Herzog, & Westheimer, 2007 ; Sayim, Westheimer, & Herzog, 2008a ; Sayim et al, 2010 ; Sayim et al, 2011 ), limiting various capacities, ranging from reading ( Pelli, Tillman, Freeman, Su, Berger, & Majaj, 2007 ; Pelli & Tillman, 2008 ), to visual search ( Carrasco, Evert, Chang, & Katz, 1995 ; Reddy & VanRullen, 2007 ; Rosenholtz, Huang, Raj, Balas, & Ilie, 2012 ; Sayim, Westheimer & Herzog, 2011 ; Vlaskamp & Hooge, 2006 ), and object recognition ( Levi, 2008 ; Pelli & Tillman, 2008 ; Wallace & Tjan, 2011 ; Whitney & Levi, 2011 ). Although crowding is usually assumed not to affect target detection ( Chung, 2010 ; Levi, Hariharan, & Klein, 2002 ; Pelli, Palomares, & Majaj, 2004 ), parts of targets or even entire targets are often lost in crowded displays ( Coates, Bernard, & Chung, 2019 ; Sayim & Taylor, 2019 ; Sayim & Wagemans, 2017 ; Taylor & Sayim, 2020 ; Yildirim, Coates, & Sayim, 2019 ; Yildirim, Coates, & Sayim, 2020 ; Yildirim, Coates, & Sayim, 2021 ; Yildirim, Coates, & Sayim, 2022 ). A particularly strong loss was found in repeating patterns, for example, when observers report only two of three presented lines ( Yildirim, Coates, & Sayim, 2020 ; Yildirim, Coates, & Sayim, 2021 ).…”
Section: Introductionmentioning
confidence: 99%